Nancy Tatom Ammerman, Studying Lived Religion: Contexts and Practices (New York: New York University Press). Pp. 255. £23.00. ISBN 1479804347. - Jensen, Mie Astrup (Religious studies, 2023)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0034412522000270/resource/name/firstPage-S0034412522000270a.jpg